The development of community learning center ‘Bue Ban’ in driving the smart city policy in Khon Kaen, Thailand - Vitthaya Thongdee; Suraphon Promgun; Suthipong Sawadtha; Somkhoun Namsithan; Phanthiwa Thubphumee; Niraj Ruangsan (Institute of Advanced Engineering and Science, 2022)
This research studied the contextual conditions of Khon Kaen Urban Community for developing the community learning center (CLC) as a part of smart city development. It also aimed to develop ‘Bue Ban’ CLC model based on the public participation and digital advancement. This study was carried out employing the qualitative and operational research method with its tools as an in-depth interview, academic seminar, and fieldwork. The data were obtained from 66 participants, chosen by purposive sampling, and were interpreted by descriptive content analysis. From the study, the models of Bue Ban development and knowledge management, identity, development, publication, utilization or ‘KID-PU’ have been used to develop CLC as a part of smart city development.